A history of Czechs and Jews : a Slavic Jerusalem - Wein, Martin Joachim, 1973- (Routledge Jewish studies series, 2015)
Was Israel founded by Czechoslovakia? A History of Czechs and Jews examines this question and the resulting findings are complex. Czechoslovakia did provide critical, secret military sponsorship to Israel around 1948, but this alliance was short-lived and terminated with the Prague Trial of 1952. Israel's "Czech guns" were German as much as Czech, and the Soviet Union strongly encouraged Czechoslovakia's help for Israel. Most importantly however, the Czechoslovak-Israeli military cooperation was only part of a much larger picture. Since the mid-1800s, Czechs and Jews have been systematically.